2006
DOI: 10.1002/path.1941
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 is activated in a subset of the Ewing sarcoma family of tumours

Abstract: STAT3 is an oncogene that regulates critical cellular processes and whose constitutive activation has been demonstrated to correlate with biological and clinical features in many types of human malignancy. In this study, STAT3 activation was assessed in the Ewing sarcoma family of tumours (ESFT), which is characterized by fusion of the EWS gene with one of several Ets transcription factors, most commonly EWS-FLI1. STAT3 activation was assessed by immunohistochemistry using a monoclonal antibody specific for ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…In a group of Ewing sarcoma family tumors with confirmed EWS translocations, we have identified only 2/47 (4.2%) EGFR-positive tumors and 11/49 (22.4%) ErbB-2-positive tumors. 39,40 Likewise, neuroblastoma tumors predominantly lack EGFR expression (J Khoury, unpublished data), and in a published survey of a large group of neuroblastoma tumors only a small subset expressed ErbB-2. 41 These data seem to suggest that the prevalence of EGFR and ErbB-2 expression is distinctly higher among rhabdomyosarcoma tumors compared to the Ewing sarcoma family of tumors and neuroblastoma.…”
Section: Discussionmentioning
confidence: 98%
“…In a group of Ewing sarcoma family tumors with confirmed EWS translocations, we have identified only 2/47 (4.2%) EGFR-positive tumors and 11/49 (22.4%) ErbB-2-positive tumors. 39,40 Likewise, neuroblastoma tumors predominantly lack EGFR expression (J Khoury, unpublished data), and in a published survey of a large group of neuroblastoma tumors only a small subset expressed ErbB-2. 41 These data seem to suggest that the prevalence of EGFR and ErbB-2 expression is distinctly higher among rhabdomyosarcoma tumors compared to the Ewing sarcoma family of tumors and neuroblastoma.…”
Section: Discussionmentioning
confidence: 98%
“…Tissue microarray slides from the Ewing sarcoma cases were analyzed by fluorescence in-situ hybridization (FISH) using a dual-color break-apart probe cocktail flanking the EWS-R1 breakpoint region (22q12) (Vysis, Downers Grove, IL, USA). 29 Tissue microarray blocks were constructed from 1 mm cores of formalin-fixed, paraffin-embedded tissue in triplicate. One tissue microarray block was produced for each tumor type, with each block containing a variety of normal and neoplastic tissue samples as internal controls.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that STAT3 is also constitutively activated in a number of human tumors, [25][26][27][28] including MCL cells, 29,30 and possesses tumorigenic potential 31 and antiapoptotic activities. 25,32 Inhibition of constitutively active STAT3 suppresses proliferation and induces apoptosis.…”
Section: Atiprimod Activated Jnk and Inhibited Nf-b And Stat3mentioning
confidence: 99%